Agricultural Development and Land use Pattern in Nashik District of Maharastra, India - Pandit, Pagar Mansaram (Richtmann Publishing, 2012)
The paper aims to analyse the agricultural development and land use pattern in Nashik district. Nasik,lying between 19o 33’ and 200 53’ north latitude and 730 16’ and 750 16’, with an area of 15530 Sq. K.M.North south length is 120 k.ms. East West length is 200 k.ms. Forest, Agricultural Land, Area not availablefor cultivation, Cultural waste is different distribution of land use pattern. The total irrigated area is 6.6 %and unirrigated area is 54.6 %.The highest irrigated area is in Niphad and lowest irrigated area is inSurgana. The highest unirrigated area in Igatpuri Tahsil. The Girna and Godavari is drained by two chiefrivers and several dams have been built across the main stream.Rafiullah’s method is use for cropcombination analysis, the nine crop combination in Dindori Tahsil , four crop combination in Yevla, threecrop combination in five tehsils that are Surgana, Kalwan, Deola, Peint, Trimbak and two cropcombination in Satana(Baglan), Malegaon, Nandgaon, and Chandvad Tahsil. Nashik has population of6,109,052 of which male and female are 3,164,261 and 2,944,791 respectively, Average literacy rate ofNashik district in 2011 are 82.91 compared to 80.96 of 2001.